2005
DOI: 10.1038/sj.pcan.4500837
|View full text |Cite
|
Sign up to set email alerts
|

Brn-3a neuronal transcription factor functional expression in human prostate cancer

Abstract: Neuroendocrine differentiation has been associated with prostate cancer (CaP). Brn-3a (short isoform) and Brn-3c, transcriptional controllers of neuronal differentiation, were readily detectable in human CaP both in vitro and in vivo. Brn-3a expression, but not Brn-3c, was significantly upregulated in 450% of tumours. Furthermore, overexpression of this transcription factor in vitro (i) potentiated CaP cell growth and (ii) regulated the expression of a neuronal gene, the Nav1.7 sodium channel, concomitantly up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
(79 reference statements)
3
29
0
Order By: Relevance
“…These hypotheses have been supported by the recent findings of Diss et al [85,86] . They found that a neuronal transcription factor (Brn-3a) (overexpressed in aggressive NE tumors and in advanced PCa) controls a voltage-gated sodium channel (Nav 1.7) expression in human PCa (upregulation).…”
Section: Biogenic Polyamine Pathways and Neurotransmitterssupporting
confidence: 80%
See 1 more Smart Citation
“…These hypotheses have been supported by the recent findings of Diss et al [85,86] . They found that a neuronal transcription factor (Brn-3a) (overexpressed in aggressive NE tumors and in advanced PCa) controls a voltage-gated sodium channel (Nav 1.7) expression in human PCa (upregulation).…”
Section: Biogenic Polyamine Pathways and Neurotransmitterssupporting
confidence: 80%
“…These androgen-independent neoplastic cells are able to increase the proliferation index (by increasing the Ki-67 positivity) of surrounding non-NE-phenotype cancer cells by the secretion of NE products through a paracrine mechanism (through transactivation of the androgen receptor) [18,75,76] .…”
Section: Autocrine/paracrine Interactionsmentioning
confidence: 99%
“…Generation of cDNA and RT-PCR was performed as described (40). See SI Materials and Methods for details.…”
Section: Methodsmentioning
confidence: 99%
“…At later stages, the disease becomes refractory to androgen ablation; however, curiously, knockdown of AR is still sufficient to inhibit the growth of androgen-independent cancers, indicating that although androgens may no longer be required, AR remains critical for survival (52,53). Intriguingly, relative to agematched controls, Brn-3a expression is elevated in prostate cancer tissue, and its expression increases with disease progression (54). Thus, in light of the interaction between Brn-3a and AR described in this work, it may be the case that late stage prostate cancers are able to use Brn-3a to increase activation of AR-regulated genes, thereby reducing the requirement for androgens.…”
Section: Discussionmentioning
confidence: 95%